1994
DOI: 10.1007/bf02245452
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke depression: combined treatment with imipramine or desipramine and mianserin

Abstract: In a 6-week study the efficacy of combined treatment of imipramine plus mianserin was compared to combined treatment of desipramine plus mianserin in patients with post-stroke depression. Patients were required to have a minimum baseline total score of 15 on the 17-item Hamilton Depression Scale (HAMD). The Melancholia Scale (MES) was also used to measure severity of depressive states to show that somatic symptoms had little influence on the evaluation of depression. Out of 120 stroke patients screened, 20 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 13 publications
1
31
0
1
Order By: Relevance
“…Both tricyclic antidepressants (TCAs) (Schiffer & Wineman, 1990) and selective serotonin reuptake inhibitors (SSRIs) (Scott, Nussbaum, McConnell, & Brill, 1995) have been used successfully in the treatment of depression associated with multiple sclerosis, stroke (Lauritzen, Bjerg Bendsen, Vilmar, Bjerg Bendsen, Lunde, & Bech, 1994), Alzheimer's disease (Gottfries, 1997;Tueth, 1995), HIV infection (Ayuso, 1994;Rabkin, Wagner, & Rabkin, 1994), and depression induced by IFN administration (e.g., in hepatitis C or multiple sclerosis patients) (Levenson & Fallon, 1993;Mohr, Goodkin, Likosky, Gatto, Baumann, & Rudick, 1997).…”
Section: Effects Of Antidepressants On Depression Induced By Immune Amentioning
confidence: 99%
“…Both tricyclic antidepressants (TCAs) (Schiffer & Wineman, 1990) and selective serotonin reuptake inhibitors (SSRIs) (Scott, Nussbaum, McConnell, & Brill, 1995) have been used successfully in the treatment of depression associated with multiple sclerosis, stroke (Lauritzen, Bjerg Bendsen, Vilmar, Bjerg Bendsen, Lunde, & Bech, 1994), Alzheimer's disease (Gottfries, 1997;Tueth, 1995), HIV infection (Ayuso, 1994;Rabkin, Wagner, & Rabkin, 1994), and depression induced by IFN administration (e.g., in hepatitis C or multiple sclerosis patients) (Levenson & Fallon, 1993;Mohr, Goodkin, Likosky, Gatto, Baumann, & Rudick, 1997).…”
Section: Effects Of Antidepressants On Depression Induced By Immune Amentioning
confidence: 99%
“…Chronic treatment with antidepressants, including fluoxetine, has been found to be effective in alleviating the depression associated with multiple sclerosis (Schiffer and Wineman 1990), stroke (Lauritzen et al 1994), HIV infection (Rabkin et al 1994), cancer (Razavi et al 1996), and neurodegenerative diseases (Alexopoulos 1996). Because these medical conditions are also associated with dramatic immune activation and cytokine secretion (Dinarello and Wolff 1993;Rothwell et al 1996;Yirmiya et al 1999), it may be suggested that at least part of the effects of fluoxetine (and possibly other antidepressants) in these conditions is in attenuating sickness behavior symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs have the advantage of being generally nonsedative and devoid of cardiotoxic, anticholinergic, and antihistaminergic effects. 1920 A further indication for using this approach is the recent finding that more effective treatment of PSD is obtained with the combination imipramine/mianserin than with desipramine/ mianserin, 21 with the greater efficacy of the former probably attributable to the serotonergic component of imipramine treatment. That the treatment of PSD with serotonin reuptake inhibitors is in fact effective is demonstrated by the present double-blind, placebocontrolled trial with citalopram in an unselected consecutive cohort of acute stroke patients with PSD diagnosed during the first year after stroke.…”
Section: Original Contributions Effective Treatment Of Poststroke Depmentioning
confidence: 99%